Coordination between RFMOs on mutual recognition of IUU vessel lists. (September 2019) - Hutniczak, Barbara
Abstract: A centralized list of vessels identified as engaged in illegal, unreported and unregulated (IUU) fishing or mutual recognition of such lists established by each regional fisheries management organization (RFMO) offers a cost-efficient way to exchange information and cooperate on eliminating illegal harvest from the global seafood supply chain. However, to date, no entity has been specifically assigned to the task of creating such centralized list or facilitating coordination on cross-listing of individual lists between RFMOs. This undermines the global effort against IUU fishing, as operators involved in illicit activities can easily move from one fishing area to another, crossing into the jurisdiction of another RFMO, where they may not be subject to restrictions resulting from the identification as an IUU fishing vessel. To understand the extent of the potential impact of this easily-solvable shortcoming, this article explores cross-listing provisions and resulting practices across 13 RFMOs that adopted measures allowing the establishment of IUU vessel lists.